2019
DOI: 10.1177/0145561319834540
|View full text |Cite
|
Sign up to set email alerts
|

Stapes Surgery for Profound Hearing Loss Secondary to Otosclerosis

Abstract: The objective of this study is to evaluate stapes surgery in patients with otosclerosis and ''profound'' hearing loss. This means they meet hearing threshold criteria for cochlear implantation (CI). We performed a retrospective study and patient questionnaire. The results from 33 patients (35 ears) were recorded (mean age: 63.6, range: 40-85). The primary outcome measure was hearing thresholds recorded before and after surgery at 0.5, 1, 2, 3, and 4 kHz. Hearing thresholds at 2 and 4 kHz were also analyzed. Gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 19 publications
(44 reference statements)
0
11
0
4
Order By: Relevance
“…Treatments administered to patients with STPHL have been extensively studied; however, they have also been overlooked. For instance, treatment with CIs and surgery for far-advanced otosclerosis have been studied thoroughly, and many studies have shown a positive impact on the QoL [ 12 , 13 ]. However, only a small proportion (5–10%) of patients with STPHL receive CIs [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Treatments administered to patients with STPHL have been extensively studied; however, they have also been overlooked. For instance, treatment with CIs and surgery for far-advanced otosclerosis have been studied thoroughly, and many studies have shown a positive impact on the QoL [ 12 , 13 ]. However, only a small proportion (5–10%) of patients with STPHL receive CIs [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…A little number of patients with otosclerosis has an audiometric profile that could justify a CI, and when history, clinical features, and radiologic imaging confirm the diagnosis, a decision has to be made between a stapedotomy with hearing aids or a CI as a first option. 3,4,6,11,12 During the past decades, numerous studies have evaluated CI as a treatment for patients affected by FAO. 12,16,17 Cochlear implant has yielded excellent results and seems to be a good treatment for patients with advanced otosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…12 When (bilateral) stapedotomy does not yield a satisfactory result, the option of CI is still open because a previous ipsilateral stapedotomy will not affect the outcome or performance of CI. 4,11,12,16,17,35 Another point to consider is that hearing aids are always advancing with technology so that the hearing improvement after stapes surgery could be more and more powerful in the future. We report, in our study, satisfactory results with regard to speech recognition (81.8% of the patients) without any significant complications.…”
Section: Discussionmentioning
confidence: 99%
“…Otosclerosis of the bony labyrinth without immobilization of the stirrup leads to sensorineural hearing loss. The disease has a long-term course and can lead to severe hypoacusis and even deafness [4][5][6]. At the initial stage of disease, hearing loss can be unilateral, later bilateral and usually asymmetrical.…”
Section: Introductionmentioning
confidence: 99%